Functional and long-lived melanocytes from human pluripotent stem cells with transient ectopic expression of JMJD3 - Chie Kobori; Ryo Takagi; Ryo Yokomizo; Sakie Yoshihara; Mai Mori; Hiroto Takahashi; Palaksha Kanive Javaregowda; Tomohiko Akiyama; Minoru S. H. Ko; Kazuo Kishi; Akihiro Umezawa (Stem Cell Research & Therapy, 2023)
Abstract Background Melanocytes are an essential part of the epidermis, and their regeneration has received much attention because propagation of human adult melanocytes in vitro is too slow for clinical use. Differentiation from human pluripotent stem cells to melanocytes has been reported, but the protocols to produce them require multiple and complex differentiation steps. Method We differentiated human embryonic stem cells (hESCs) that transiently express JMJD3 to pigmented cells. We investigated whether the pigmented cells have melanocytic characteristics and functions by qRT-PCR, immunocytochemical analysis and flow cytometry. We also investigated their biocompatibility by injecting the cells into immunodeficient mice for clinical use. Result We successfully differentiated and established a pure culture of melanocytes. The melanocytes maintained their growth rate for a long time, approximately 200 days, and were functional. They exhibited melanogenesis and transfer of melanin to peripheral keratinocytes. Moreover, melanocytes simulated the developmental processes from melanoblasts to melanocytes. The melanocytes had high engraftability and biocompatibility in the immunodeficient mice. Conclusion The robust generation of functional and long-lived melanocytes are key to developing clinical applications for the treatment of pigmentary skin disorders.